Insecticidal effects of two medicinal plants Polygonum hydropiper L. and Abrus precatorius L. leaves against the rice weevil Sitophilus oryzae L. (Coleoptera: Curculionidae) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
During the study, the leaves of two medicinal plants, Polygonum hydropiper and Abrus precatorius were extracted with water, ethanol, methanol and petroleum ether solvents and tested against the rice weevil S. oryzae L. for insecticidal properties. Response varied with plant species. The mortality of adults increased with increasing dose concentrations from 1000 ppm to 5000 ppm each solution, with an exposure time of 72 hours. LC50 values calculated were found to be 15091.436 ppm with water, 5051.534 ppm with ethanol, 5111.063 ppm with methanol and 4305.348 ppm with petroleum ether extracts of P. hydropiper and 9687.292 ppm with water, 6263.849 ppm with ethanol, 4682.683 ppm with methanol and 3222.984 ppm with petroleum ether extracts of Abrus precatorius leaves corresponding their concentrations of the leaf extract solutions at 1000ppm, 2000 ppm, 3000 ppm, 4000 ppm and 5000 ppm respectively. The results of the study showed that methanol and petroleum ether extrcts of P. hydropiper and ethanol, methanol and petroleum ether extracts of A. precatorius showed good toxicity. It appeared that the leaf extracts had some insecticidal activities against S. oryzae adult.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 107-114